PREVALENCE AND RISK FACTOR OF POLYCYSTIC OVARIAN SYNDROME - Qureshi, Shaiba Sana; Gupta, Jeetendra Kumar; Shah, Kamal; Upmanyu, Neeraj (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Polycystic ovarian syndrome (PCOS) is the most common endocrine disorder in women. Its clinical manifestation varies from mild to severe disturbance of reproductive and metabolic functions. PCOS is clinical and public health importance because it is affecting up to one in five women of reproductive age. It is an X-linked dominant condition and has diverse clinical implications such as psychological features (anxiety, depression), reproductive features (hirsutism and hyperandrogenism), and impaired glucose tolerance. It is widely dependent on environmental, genetic, ethnicity factors including lifestyle and body weight. Weight loss improves the endocrine profile and increases chances of ovulation and pregnancy. It can be treated with medications such as clomiphene citrate, tamoxifen, aromatase inhibitors, and gonadotrophins. The last option for fertilization is in vitro fertilization when other treatment fails. Its prevalence is estimated at 4-8% from studies performed in Spain and USA. Lifestyle including diet, exercise, and behavior therapy improves fertility. PCOS has unique interactions with the ever increasing obesity prevalence worldwide as obesityinduced insulin resistance significantly aggravates all the features of PCOS. Education about how PCOS affects long-term health should be provided to women with this disorder to feel physical and psychological benefits so that they could engage themselves more with their health care providers. Keywords: Polycystic ovarian syndrome, Hyperinsulinemia, Hormone disbalance, Hirsutism, Ovarian cyst, Obesity, Sleep disorders.